Key to the species of parasitoids and hyperparasitoids (Hymenoptera) of aphids (Hemiptera: Aphididae) of Costa Rica - Zamora Mejías, Daniel; Hanson, Paul E. (Agronomía Mesoamericana, 2017)
Aphids represent a major problem for many plant species, due to their ability to serve as pathogen vectors; the use of parasitoids as biological control agents might be a suitable option for long term control of their populations. The objective of this study was to prepare a taxonomic key in order to identify parasitoids and hyperparasitoids of aphids obtained in Costa Rica. In total, during 2008 to 2015, 3009 hymenopteran parasitoids were reared from 25 species of aphids, 2832 (94%) were primary parasitoids and 175 (6%) were hyperparasitoids. A taxonomic key was made for the identification of nine species of primary parasitoids, Braconidae-Aphidiinae, Aphelinidae, Eulophidae, and six species of hyperparasitoids in five families. In addition, the genus Quadrictonus (Aphidiinae), was included in the key and was reported for the first time in this study in Costa Rica.